Rostral Agranular Insular Cortex Lesion with Motor Cortex Stimulation Enhances Pain Modulation Effect on Neuropathic Pain Model. (19th October 2016) - Jung, Hyun Ho; Shin, Jaewoo; Kim, Jinhyung; Ahn, Seung-Hee; Lee, Sung Eun; Koh, Chin Su; Cho, Jae Sung; Kong, Chanho; Shin, Hyung-Cheul; Kim, Sung June; Chang, Jin Woo
Abstract : It is well known that the insular cortex is involved in the processing of painful input. The aim of this study was to evaluate the pain modulation role of the insular cortex during motor cortex stimulation (MCS). After inducing neuropathic pain (NP) rat models by the spared nerve injury method, we made a lesion on the rostral agranular insular cortex (RAIC) unilaterally and compared behaviorally determined pain threshold and latency in 2 groups: Group A (NP + MCS; n = 7 ) and Group B (NP + RAIC lesion + MCS; n = 7 ). Also, we simultaneously recorded neuronal activity (NP; n = 9 ) in the thalamus of the ventral posterolateral nucleus and RAIC to evaluate electrophysiological changes from MCS. The pain threshold and tolerance latency increased in Group A with "MCS on" and in Group B with or without "MCS on." Moreover, its increase in Group B with "MCS on" was more than that of Group B without MCS or of Group A, suggesting that MCS and RAIC lesioning are involved in pain modulation. Compared with the "MCS off" condition, the "MCS on" induced significant threshold changes in an electrophysiological study. Our data suggest that the RAIC has its own pain modulation effect, which is influenced by MCS.